1986
DOI: 10.6028/jres.091.032
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Kilogram Capacity Calorimeter for Heterogenous Materials

Abstract: A large capacity calorimeter was designed and constructed in order to determine the enthalpies of combustion of kilogram-size samples of municipal solid waste (MSW) in flowing oxygen near atmospheric pressure. The combustion of the organic fraction of the samples was complete to greater than 99.9+%. The percent coefficient of variation (100 X standard deviation/average), % ev.of calibration measurements using microcrystalline cellulose was 0.2%. The % CV of the measurements of the enthalpy of combm.tion of a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Energy of the propellant that it submits to the system is vital for propulsion system. In order to determine the amount of energy delivered by the fuel, its enthalpy of combustion has to be measured [26][27][28]. For fuel that are formulated with the gelling agent consists of two basic compounds, firstly the parent fuel and secondly the gelling agent.…”
Section: Enthalpy Of Combustionmentioning
confidence: 99%
See 2 more Smart Citations
“…Energy of the propellant that it submits to the system is vital for propulsion system. In order to determine the amount of energy delivered by the fuel, its enthalpy of combustion has to be measured [26][27][28]. For fuel that are formulated with the gelling agent consists of two basic compounds, firstly the parent fuel and secondly the gelling agent.…”
Section: Enthalpy Of Combustionmentioning
confidence: 99%
“…The gross calorific values of the parent fuel (liquid) with respect to the formulated gel and metalized gel propellant along with thickening agent are considered using Oxygen 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 Bomb Calorimeter [26][27][28] and are given in Figures 2 and 3. The results obtained are the average of at least four sets of experiments.…”
Section: Enthalpy Of Combustionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, corrections due to carbon monoxide formation, water evaporation, and gas heating can be as high as 1.5%. The combined corrections amount to about a 5.5% change in the enthalpy of combustion obtained from the temperature rise of the calorimeter fluid [6].…”
Section: Flow Calorimetrymentioning
confidence: 99%
“…This instrument has been used in heats of combustion studies [3] and in investigations on the fate of chlorine during combustion [4,5]. Details of the design and operation of the multi-kilogram capacity flow calorimeter used in these studies can be found in the publication by Churney and coworkers [6].…”
Section: Introductionmentioning
confidence: 99%